Redefining diagnostic parameters: the role of overvaluation of shape and weight in binge-eating disorder: a systematic review - Bernou Melisse; Alexandra Dingemans (Journal of Eating Disorders)
Abstract Introduction Overvaluation of shape and weight is a critical component in understanding and diagnosing eating disorders. While the transdiagnostic model states that overvaluation of shape and weight is the core pathology of all eating disorders, this concept is not a criterion for binge-eating disorder. The lack of recognition of overvaluation of shape and weight may lead to overlooking, and consequently failure to address this construct during treatment. The aim of the present review is to examine whether overvaluation is a critical component in understanding and diagnosing binge-eating disorder and whether it should be addressed during treatment, and therefore be added as a criterion of binge-eating disorder. Methods The present review was registered in the International Prospective Register of Systematic Reviews (registration number: CRD42024541433). PsycINFO, Web of Science, PubMed (Medline), and Google Scholar were used in order to systematically search and review literature by using a list of keywords related to overvaluation of shape and weight and binge-eating disorder. All N = 93 peer-reviewed studies were published in English from 1993 onwards. Results Overvaluation of shape and weight was more severe among individuals with binge-eating disorder compared to individuals with solely a similar high BMI. In addition, levels of overvaluation in binge-eating disorder were comparable in severity with that of individuals of the other named eating disorder subtypes. Overvaluation was positively associated with other psychiatric symptoms, a risk factor for the onset of binge eating in adolescents and predicted poorer treatment outcomes. It was not clear whether overvaluation predicted dropout from Cognitive Behavior Therapy interventions. Discussion It is suggested to consider including overvaluation of shape and weight as a criterion for the diagnosis of binge-eating disorder. Including overvaluation in the DSM and ICD may prevent overlooking this construct, and potentially enhance treatment outcomes. Plain English summary It is suggested that overvaluation of shape and weight is the core pathology of all eating disorders. However, this concept is not a criterion for a binge-eating disorder diagnosis. The lack of recognition of overvaluation of shape and weight may lead to overlooking, and consequently failure to address this construct during treatment. The aim of the present review is to examine whether overvaluation is a critical component in understanding and diagnosing binge-eating disorder and whether it should be addressed during treatment, and therefore be added as a criterion of binge-eating disorder. Consequently, a total of N = 93 peer-reviewed studies were examined. It was found that overvaluation of shape and weight was associated with the severity of eating disorder psychopathology, and was comparable in severity with that of individuals diagnosed with anorexia nervosa and bulimia nervosa. There is enough evidence to include overvaluation in the DSM and ICD as a criterion for binge-eating disorder. Consequently, this may prevent overlooking this construct, and potentially enhance treatment outcomes.